2011
DOI: 10.1111/j.1365-2141.2011.08949.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of lenalidomide/dexamethasone versus cyclophosphamide/lenalidomide/dexamethasone versus cyclophosphamide/bortezomib/dexamethasone in newly diagnosed multiple myeloma

Abstract: Summary Novel agents are considered standard components of induction therapy for newly diagnosed patients with multiple myeloma. We retrospectively compared the results of three consecutive phase 2 clinical trials; RD (lenalidomide/dexamethasone, n = 34), CRD (cyclophosphamide/lenalidomide/dexamethasone, n = 53) and CyBorD (cyclophosphamide/bortezomib/dexamethasone, n = 63) (N = 150). Response rates after four cycles of treatment were: ≥near complete response (nCR), 12% vs. 2% vs. 41%, P < 0·0001 and very good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 31 publications
4
32
0
Order By: Relevance
“…Another common induction combination is lenalidomide and dexamethasone (RD). A comparison of RD, CyBorD and CRD showed similar survival at 3 years, but there are no prospective randomized trials comparing these regimens (Khan et al, 2012). In a recent analysis of patients treated with RD, the 5-year survival was 71%, similar to our patients teated with CyBorD (Srivastava et al, 2013).…”
supporting
confidence: 72%
“…Another common induction combination is lenalidomide and dexamethasone (RD). A comparison of RD, CyBorD and CRD showed similar survival at 3 years, but there are no prospective randomized trials comparing these regimens (Khan et al, 2012). In a recent analysis of patients treated with RD, the 5-year survival was 71%, similar to our patients teated with CyBorD (Srivastava et al, 2013).…”
supporting
confidence: 72%
“…These differences were not the result of dose attenuation or the use of a "VCD-light" regimen, as the dose of cyclophosphamide that was administered in our trial was 500 mg/m 2 on days 1, 8, and 15, which is higher than that reported in the retrospective study by Cavo et al (500 mg/ 2 on days 1 and 8) 16 or in other VCD regimens reported previously. [6][7][8] The dose intensity in both arms was high and was greater than 90% for each drug. The VGPR rate of 56% with VCD described in our trial (ITT) is much higher than the 37% VGPR rate reported by Mai et al in the prospective German trial 12 and the 37% VGPR rate that was reported by Cavo et al in the retrospective Italian analysis.…”
Section: Discussionmentioning
confidence: 98%
“…4 Based on response rates, depth of response, and PFS as surrogate markers for outcome, 3-drug combinations including bortezomib and dexamethasone plus either an immunomodulatory drug (IMiD) (thalidomide or lenalidomide), cyclophosphamide, or doxorubicin (PAD) are currently the standard of care prior to ASCT. [1][2][3][4][5] The triplet combinations bortezomibthalidomide-dexamethasone (VTD) and bortezomib-cyclophosphamidedexamethasone (VCD) have demonstrated high response rates in prospective phase 2 [6][7][8] and phase 3 [9][10][11][12] clinical trials, they are two of the most commonly used induction regimens prior to ASCT and are both recommended in the international guidelines. [1][2][3] To date, no comparative data from prospective randomized trials of the safety and efficacy of VTD vs VCD are available.…”
Section: Introductionmentioning
confidence: 99%
“…Since this study was designed, data on new triple-combination induction therapies and novel emerging treatments have been published. For example, at least four new bortezomib-based triple combinations: bortezomib-thalidomide-dexamethasone (VTD), bortezomib-lenalidomide-dexamethasone (RVD), bortezomibdoxorubicin-dexamethasone (PAD), and cyclophosphamide-bortezomib-dexamethasone (CyBorD) have been described previously (25)(26)(27)(28)(29)(30). In terms of novel emerging treatments, phase I/II trials have investigated inductionmaintenance regimens including the two new proteasome inhibitors carfilzomib (carfilzomib-lenalidomide-dexamethasone induction with lenalidomide maintenance, and carfilzomib-cyclophosphamide-dexamethasone with carfilzomib maintenance) and ixazomib (ixazomib-lenalidomide-dexamethasone induction with ixazomib maintenance), and the histone deacetylase inhibitor vorinostat (RVD-vorinostat with lenalidomide AE bortezomib maintenance; refs.…”
Section: Discussionmentioning
confidence: 99%